2022
DOI: 10.1038/s41522-022-00330-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of oropharyngeal microbiome among SARS-CoV-2 patients reveals continued dysbiosis even after Viral Clearance

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has posed multiple challenges to global public health. Clinical features and sequela of SARS-CoV-2 infection include long-term and short-term complications often clinically indistinguishable from bacterial sepsis and acute lung infection. Post-hoc studies of previous SARS outbreaks postulate secondary bacterial infections with microbial dysbiosis. Oral microbial dysbiosis, particularly the altered proportion of Firmicutes and Proteobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
1
9
0
1
Order By: Relevance
“…Our results also showed that the oropharyngeal microbiota in patients with severe HFMD was predominant in several bacterial genera, including Stenotrophomonas , Prevotella, and Streptococcus . The results are in line with several recent studies on oropharyngeal microbiota of patients with COVID-19 [ 41 , 42 ]. These bacteria were also observed in influenza virus-infected patients who often had secondary bacterial pneumonia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results also showed that the oropharyngeal microbiota in patients with severe HFMD was predominant in several bacterial genera, including Stenotrophomonas , Prevotella, and Streptococcus . The results are in line with several recent studies on oropharyngeal microbiota of patients with COVID-19 [ 41 , 42 ]. These bacteria were also observed in influenza virus-infected patients who often had secondary bacterial pneumonia.…”
Section: Discussionsupporting
confidence: 92%
“…Streptococcus is one of the most prevalent inhabitants of the oropharynx and respiratory tract of adults and children. Recent study has reported the reduction in proportion of Streptococcus and Velionella in COVID-19-infected patients compared to healthy control [ 41 ]. Prevotella members exhibit pro-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 43 COVID-19 patients (24 Delta and 19 Omicron) and 19 HC were recruited in this study. All 19 Omicron and 5 of the delta samples were collected by the clinicians of COM&JNM Hospital in Kalyani from December 2021 to January 2022 and the rest of the 19 Delta samples were collected from ICMR-Regional Medical Research Centre, Bhubaneswar during the COVID second wave and published recently by members of our group ( 28 ). Healthy controls were collected from Kalyani during November–Dec 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Since the start of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) war, as of December 2021, COVID-19 has spread to 222 countries, resulting in more than 260 million con rmed cases and more than 5 million deaths worldwide 9 .The most common long-term effects and adverse consequences of SARS-CoV-2 infection are sepsis, pneumonia, and other pulmonary infections In fact, in addition to the possible direct infection of the heart muscle and other types of cardiovascular cells, the novel coronavirus can also mediate immune responses and in ammation, thus causing severe damage and dysfunction of the cardiovascular system.In the acute phase, the incidence of major all-cause cardiovascular diseases and mortality of COVID-infected patients increased signi cantly. Compared with uninfected patients, the risk of various cardiovascular diseases after "Yang" increased signi cantly by 330%, and the risk of allcause death was 81.1 times that of the former.…”
Section: Discussionmentioning
confidence: 99%